La consulta popular en México: un replanteamiento para superarlainoperabilidad a la luz de los primeros resultados y los modelos Latinoamericanos. - López Sáenz, Emanuel (Universidad Autónoma de Nuevo León - UANL, 2017)
The figure of popular consultation recently emerged in the Mexican legal framework alongside the citizen initiative and the independent governments.By virtue of this new tool of democratic participation, it is necessary to question about the efficiency of it (a question that must be analyzed in the other two), assesing the aspects to be improved –if applicable-in order to give full validity to the emphatic attempt, to create more solid links between the government and the participation of its citizens, condition that strengthens a country’s governance.This approach arises, since an analysis of the fisrt cases to conduct varied popular consultations in the electoral day from 2015 was done and all the requests studied were dismissed by the Highest Court, who is previously in charge of the analysis of the constitutionality of the consultations, stating that, all the raised issues were prohibited by the Constitution.This has led to a recent debate in different latitudes about the suitability of reformulate the figure, since it is nowadays a model of participation that seeks to empower the citizen, however, from the 2015 experience and with the aim of providing full validity to the civilian right of participating, is convenient to study the constitutional limitations not to plumb in the depths of absurdity having on one side the constitutional requirement of national transcendence, an on the other hand, theinconstitutionality and therefore the inoperativity of the consultation by the extent of the contitutional restrictions. For all these reasons, a methodological study of comparative law was initiated, for purposes of studyng the regulations and best practices from countries that already count with similar consultation figures, which cast some conclusions.